A Tradução como Programa e Construção: o Abraço ao Universo Literário de Língua Inglesa em Duas Coleções de Livros da Editora Romano Torres - Medeiros, Nuno (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
Departing from two book series almost exclusively focused on Anglophone literature this article explores how Romano Torres, a Portuguese publishing house without any significant prior vocation of printing works translated from English, makes its way in publishing books from this particular linguistic world. The actions taken by the publisher, including by those collaborators who played a relevant part in the two book series, illustrate the participation of these agents in the social process of cultural creation and configuration, through their role as cultural mediators and gatekeepers. In one of the cases analysed, the collection Obras Escolhidas de Autores Escolhidos [Selected Works from Selected Authors], the active presence of both publisher and associates in shaping the books is strikingly evident, strategically aiming at establishing the idea of a canon and even intervening in the textual content itself.